PENGARUH COUNTRY OF ORIGIN, BRAND IMAGE DAN PERSEPSI KUALITAS TERHADAP INTENSI PEMBELIAN - Magyar Slamet Permana; Jony Oktavian Haryanto (Jurnal Manajemen., 2014)
At present, the development of technology becomes intense among notebook manufacturers. They compete to create advantages in product markets. When people buy a product, consumers do not just look at the advantages it offers, but they also see its brand. Country of origin, brand image, and perceived quality influence people to make decision to buy a product. This study aims to determine the effect of country of origin, brand image, perceived quality on the purchase intentions of the Lenovo notebook. The study involved 150 respondents and the data was tested using structural equation modeling with Lisrel 8.7 software. The result findings showed that country of origin affect brand image, perceived quality and purchase intentions. In addition, this study showed that brand image has an effect on perseived quality. In the future, PT. Lenovo Indonesia as a subsidiary of Lenovo Group Limited needs to build a force to strengthen the Lenovo brand in marketing its product in the Indonesian market.